Flavor quality evaluation of Pixian Douban fermented in the closed system of multi-scale temperature and flow fields. (15th June 2022) - Liu, Yan; Zhang, Yimao; Shi, Yujiao; Zhang, Manna; Liu, Yi; Che, Zhenming; Lin, Hongbin; Lv, Guangyuan; Zhu, Qi; Dong, Shirong; Ding, Wenwu
Abstract: In this study, a material of pseudoplastic fluid was obtained by dealing with the original material of Pixian Douban (PXDB). The multi-scale temperature and flow fields (MTFF) were established, and a PXDB product fermented in the MTFF (PFM) was obtained. Meanwhile, the material of pseudoplastic fluid and the original material was also fermented into PXDB products named MPTF and OMP, respectively, following the traditional process. The contents of major physicochemical indexes, organic acids and free amino acids in the PFM were higher than those in the MPTF and OMP. A total of 112, 102, 105 volatile compounds were detected in the PFM, MPTF and OMP. The PFM was rich in esters and alcohols while MPTF was abundant in aldehydes. The PFM possessed higher soy sauce-like, umami, sour taste and sour smell by quantitative descriptive analysis (QDA). The PFM was positively correlated with many indexes by partial least squares discriminant analysis (PLS-DA), such as all physicochemical properties, Asp, Glu, C3 and A8. These results indicated that the flavor of PFM was richest, which showed that a PXDB product with higher quality could be obtained in MTFF. Highlights: A kind of PXDB named PFM was fermented in multi-scale temperature and flow fields. The contents of physicochemical indexes, OAs and FAAs in the PFM were the highest. The PFM was rich in esters and alcohols while MPTF was abundant in aldehydes. The PFM possessed a higher soy sauce-like, umami, sour taste and sour smell by QDA. A kind of PXDB product with higher quality could be obtained in MTFF.